Motivation in second language acquisition: A bibliometric analysis between 2000 and 2021 - Wu, Xue (Frontiers in Psychology, 2022)
As one of the most important constructs of individual differences in second language learning, motivation has garnered a lot of attention in the area of Second Language Acquisition (SLA). Nevertheless, little bibliometric research has been conducted to provide a systematic overview of this line of research, which will help researchers to better understand how motivation-related research in SLA has evolved over the last years and where it might push the boundaries of SLA research into in the future. In this study, three types of bibliometric analyses (i.e. co-citation analysis, citation analysis, and keyword analysis) were performed to identify the prominent scholarly documents, authors, venues of publications, and research topics that have been highly influential in the research of motivation in SLA between 2000 and 2021. Results from scientific network maps and keyword analysis suggest significant changes on the topic over the past 22 years. The results in this study also indicates an evident continuity of theoretic development in L2 language learning motivation research. Moreover, an air of active use of qualitative approaches has been detected in L2 language learning motivation research in the last 22 years.